The Lagrangian Stability for a Class of Second-Order Quasi-Periodic Reversible Systems - Yanling Shi; Jia Li (Abstract and Applied Analysis)
We study the following two-order differential equation, (Φp(x'))'+f(x,t)Φp(x')+g(x,t)=0, where Φp(s)=|s|(p-2)s, p>0. f(x,t) and g(x,t) are real analytic functions in x and t, 2aπp- periodic in x, and quasi-periodic in t with frequencies (ω1,…,ωm). Under some odd-even property of f(x,t) and g(x,t), we obtain the existence of invariant curves for the above equations by a variant of small twist theorem. Then all solutions for the above equations are bounded in the sense of supt∈R|x′(t)|<+∞.